Lifestyle treatment in women with polycystic ovary syndrome: predictors of weight loss and dropout. Issue 7 (2nd June 2022) - Jiskoot, Geranne; Dietz de Loos, Alexandra; Timman, Reinier; Beerthuizen, Annemerle; Laven, Joop; Busschbach, Jan
Abstract: Background: Polycystic ovary syndrome (PCOS) affects 5%–10% of women in their reproductive years. Most women with PCOS struggle with obesity during their entire life. Knowing which determinants contribute to a successful lifestyle change is important to optimize treatment options for women with PCOS. Objective: This analysis of secondary outcome measures aimed to determine factors of ≥5% weight loss and dropout in all arms of the study and separately in the lifestyle intervention (LI) and control (care as usual [CAU]) groups. Study design: Women diagnosed with PCOS ( N = 183) and a Body Mass Index (BMI) above 25 kg/m 2 were included. Participants were assigned to (1) 20 lifestyle sessions involving cognitive behavioral therapy (CBT), (2) 20 lifestyle sessions involving CBT with additional short message service (SMS), or (3) to control (CAU). A generalized linear regression was performed to identify determinants of ≥5% weight loss. Logistic regression was performed to identify determinants of dropout. All models were corrected by including baseline weight as a covariate. Results: LI (OR 4.906, p = .001) was associated with ≥5% weight loss, while higher depression scores (OR 0.549, p = .013) had a negative association. Restraint eating was a positive factor for ≥5% weight loss in LI but a negative in CAU. Higher baseline weight (OR 1.033, p = .006), LI with SMS (OR 4.424, p = .002), and higher levels of androstenedione (OR 1.167, p = .026) were associated with dropout. Conclusions: Depression and eating behavior were associated with ≥5% weight loss. Women with PCOS should be screened for depression and eating behavior before a LI.